Study the Structure Properties of CdTe and CdTe/CdSe Quantum Dots at pH=12 using an Aqueous Method - Noori, Husham. N.; Abdulameer, Ameer F. (Iraqi Journal of Science, 2024)
This research aims to study the structural properties of cadmium telluride (CdTe) core QDs and cadmium telluride/ cadmium selenium (CdTe/CdSe) core-shell QDs at pH 12. The QDs were prepared using aqueous synthesis by reflux process. The structural properties of the QDs were studied using X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-ray spectroscopy (EDX), and Transmission Electron Microscopy (TEM). The results of the XRD analysis for CdTe QDs and CdTe/CdSe QDs showed that they have three diffraction peaks in the directions (111), (220), and (331) with a slight shift in the diffraction peaks of CdTe/CdSe QDs, which indicates the successful packing of selenium atoms around CdTe. FESEM results confirmed that CdTe and CdTe/CdSe QDs possess quantum spherical NPs with diameters ranging from 27 nm to 41 nm. The EDX results confirm corrections of added concentrations The histogram images of the TEM analysis show that the diameters of CdTe and CdTe/CdSe are 7nm and 9 nm, respectively.